She's all that! : a look-it-up guide to the goddesses of mythology - Bryant, Megan E. (New York : Scholastic, 2009)
Presents a guide to Greek mythology, providing profiles of goddesses and the myths surrounding them.
Z
940
Z
Keywords: Goddesses -- Dictionaries, Juvenile